Multiaxial pulsatile dynamics of the thoracic aorta and impact of thoracic endovascular repair. (2021) - Suh, Ga-Young; Bondesson, Johan; Zhu, Yufei D.; Lee, Jason T.; Dake, Michael D.; Cheng, Christopher P.
Highlights: Altered motion of the thoracic aorta after thoracic endovascular aortic repair. Geometric analysis with cardiac-gated computed tomography and computer modeling. Decreased motion of the stented aorta and increased motion above the stented aorta. Longitudinal curvature and diametric deformation affected by presence of endograft. Abstract: Purpose: The thoracic aorta is a highly mobile organ whose dynamics are altered by thoracic endovascular aorta repair (TEVAR). The aim of this study was to quantify cardiac pulsatility-induced multi-axial deformation of the thoracic aorta before and after descending aortic TEVAR. Methods: Eleven TEVAR patients (8 males and 3 females, age 57–89) underwent retrospective cardiac-gated CT angiography before and after TEVAR. 3D geometric models of the thoracic aorta were constructed, and lumen centerlines, inner and outer surface curves, and cross-sections were extracted to measure aortic arclength, centerline, inner surface, and outer surface longitudinal curvatures, as well as cross-sectional effective diameter and eccentricity for the ascending and stented aortic portions. Results: From pre- to post-TEVAR, arclength deformation was increased at the ascending aorta from 5.9 ± 3.1 % to 8.8 ± 4.4 % (P < 0.05), and decreased at the stented aorta from 7.5 ± 5.1 % to 2.7 ± 2.5 % (P < 0.05). Longitudinal curvature and diametric deformations were reduced at the stented aorta. Centerline curvature, inner surface curvature, and cross-sectional eccentricity deformations were increased at the distal ascending aorta. Conclusions: Deformations were reduced in the stented thoracic aorta after TEVAR, but increased in the ascending aorta near the aortic arch, possibly as a compensatory mechanism to maintain overall thoracic compliance in the presence of reduced deformation in the stiffened stented aorta.